(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
Security at the present time is very important and highly effective for Internet and network applications, which are rapidly growing, therefore the data that is exchanged over the Internet or other media has increased in value and importance. Therefore, the process of searching for the best solutions for the purpose of providing the required protection against illegal attacks with the provision of these services in a timely manner is one of the most interesting topics in security-related communities. This paper aims to test a number of symmetric encryption algorithms (AES, DES, 3DES, RC4, Blowfish, Twofish) with security mode cipher block chaining (CBC). A comparison is then made between them based on evaluation criteria: encryption and decryption time tests are implemented by using Java programming language. The randomness test on ciphertext, which was implemented by using the Diehard statistical test to compute the most efficient algorithm to use in various life applications. The results of the paper showed that the 3DES algorithm is the most time-consuming, followed by DES, while RC4 is the algorithm that needs the least execution time, followed by AES, and both Twofish and Blowfish came between these two levels. As for the randomness criterion, 3DES was the best compared to the rest of the algorithms, while RC4 and AES were the worst in this criterion.